Strategies to Create Literacy Culture during the Covid-19 Pandemic: A Case Study of Public Library in Pesisir Selatan Regency, Indonesia - Jafri, Titania Elvindry; Wigati, Dewi Endah (Indonesian Journal of Librarianship, 2022)
Background: From year to year, the people of Pesisir Selatan Regency have low literacy. This situation actually opens up an opportunity to create literacy culture in line with the National Literacy Movement during the Covid-19 pandemic in Pesisir Selatan Regency. Objective: This study investigates the strategies used by the Public Library of Pesisir Selatan Regency in creating literacy during the Covid-19 pandemic. Method: This study uses a descriptive qualitative research method. The data collection was obtained from documentation, participatory observation, and interviews. Meanwhile, the data were analyzed using SWOT analysis. Results: The findings show that in order to create literacy in Pesisir Selatan Regency, there are several programs carried out to support non-digital literacy and digital literacy; Finding on strength dimension is the availability of library facilities and infrastructure; Findings on weakness dimension are lack of library collections and lack of skilled librarians; Findings on opportunity dimension are high potential of library partner community activities and high public visits during online learning policy (public library is used as a non-formal learning space); and Finding on threat dimension is the rapid development of technology. Conclusion: This research suggests that strategies used in creating literacy for Pesisir Selatan Regency during the Covid-19 pandemic are maximizing facilities to improve the library services; enhancing the librarians and the library staffs’ skills; adding more collection of books and more diverse reading materials; using social media and reading ambassadors to promote literacy culture; as well as implementing digital-based library transformation and digital literacy reinforcement for librarians and the library visitors. Keywords: Creating Literacy Culture; Covid-19 Pandemic; Public Library of Pesisir Selatan Regency; Strategies